Insersi dan Delesi Intron Satu Gen Rhodopsin (RDP1) Nukleus Kelompok Burung Megapoda (Aves megapodiidae) Indonesia - Budiarsa, I Made (Universitas Syiah Kuala, 2011)
Insertion and deletion are information that reflect evolutional potency of species or population, that nowadays, are central topics in conservation genetics. This research aims to reveal the proportion of insertion and deletion on RDP1of species Megapodes in Indonesia. Whole blood DNA was extracted according to the protocol of Qiamp DNA Blood Mini Kit (Qiagen), and used as template for PCR (Polymerase Chain Reaction) which was conducted according the protocol of Takara Ex TaqTM PCR Kit in a Perkin-Elmer Thermal Cycler 9600. PCR products were purified using a Qiaquick PCR Purification Kit (Qiagen, USA). The sequencing reaction for RDP1 was performed using BigDye v.3.1. Cycle Sequencing Kit (Applied Biosystems,USA) followed the protocol of ABI Prism 3100-Avant Genetic Analyzer (Applied Biosystems, USA). Alignment of RDP1 nucleotide sequences of megapodes and that are obtained from international DNA data base (DDBJ-DNA Data Bank of Japan) with accession number AF 394649 (RDP1) were conducted by using Clustal-X. Characteristics of RDP1 were analyzed by employing the DNA Sequence Polymorphism (DnaSP) version 3.51 and Program MEGA version 4. The analysis result demonstrated there were insertion and deletion on RDP1 of species of Megapodes in Indonesia, which resulting in a gap of 1-10 bp and was concentrated in nucleotide 407-568. Alignments between species of Megapodes and two species of Galliformes showed more gaps, which were concentrated on nucleotides 480-708.